(3GUhd GdScQJGQjI GdJWHjbjI (B/s - (3Rhjd, eMeO Gejfs ((3GdGScfOQjI(B: s (3ecJHI GdeYGQa GdMOjKI(B, s)
(3ChdG GdegGQGJ GdYGeI egGQGJ GdMOjK ; egGQGJ GdeTGQcI aj GdefGbTGJ ; egGQGJ GdMUhd Ydi GdeYdheGJ , egGQGJ GdQO Ydi GdJdjahf hGSJNOGeg eMdjG hOhdjG , egGQGJ MSf GdGSJeGY , egGQGJ bQGAI GdeQGSdGJ, egGQGJ bQGAI GdaGcSGJ egGQGJ GdbQGAI GdJaUjdjI , egGQGJ GdfXGe hGdJQJjH egGQGJ QhM GdaQjb KGfjG (B: (3GdegGQGJ GdJNUjUjI egGQGJ GdJOhjf HSLdGJ GdHQjO , egGQI Yed hJWHjb CfXeI GdagQSI , egGQGJ MaX GdeSJfOGJ hGdedaGJ , egGQGJ MaX GdeSJfOGJ hGdedaGJ , egGQGJ GdGSJOdGd ,egGQI af cJGHI eQGSdGJ GdJLGQI GdOGNdjI , egGQGJ GYOGO GdahGJjQ , egGQI cJGHI GdJbGQjQs
(3HjHdjhZQGajG (B: (3U(B.141s
Keywords: (3GdScQJGQjI(B- (3egfIs